Monte Carlo Simulation to Predict Rock Fragmentation Results from Blasting Activity at Quarry PT. Semen Padang - Muhammad Hazwafi Ardeva; Mulya Gusman; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2024)
One aspect and factor that is very important in the blasting stage is rock fragmentation, which has a direct impact on drilling costs, blasting costs and operational economics, both loading, transportation and crushing. As time progresses, new technological advances for the application of blasting have developed. This technology is to computerize blast design and predict the results of the explosion, which is rock fragmentation. Many factors influence rock fragmentation, such as the nature of the rock mass, geological location conditions, explosion and fracture parameters present in place, so it is difficult to predict completely. However, empirical models to predict the size distribution of rock fragmentation have been developed. In this study, Monte Carlo simulation as a rock fragmentation simulator based on the Kuz-Ram fragmentation model has been developed to predict fragmentation size distribution. The results obtained from this Monte Carlo simulation can be said to be quite good when compared with the actual data fragmentation obtained from field conditions.